Gap Junctional Communication via Connexin43 between Purkinje Fibers and Working Myocytes Explains the Epicardial Activation Pattern in the Postnatal Mouse Left Ventricle - Olejnickova, Veronika; Kocka, Matej; Kvasilova, Alena; Kolesova, Hana; Dziacky, Adam; Gidor, Tom; Gidor, Lihi; Sankova, Barbora; Gregorovicova, Martina; Gourdie, Robert G; Sedmera, David (International journal of molecular sciences, 2021)
The mammalian ventricular myocardium forms a functional syncytium due to flow of electrical current mediated in part by gap junctions localized within intercalated disks. The connexin (Cx) subunit of gap junctions have direct and indirect roles in conduction of electrical impulse from the cardiac pacemaker via the cardiac conduction system (CCS) to working myocytes. Cx43 is the dominant isoform in these channels. We have studied the distribution of Cx43 junctions between the CCS and working myocytes in a transgenic mouse model, which had the His-Purkinje portion of the CCS labeled with green fluorescence protein. The highest number of such connections was found in a region about one-third of ventricular length above the apex, and it correlated with the peak proportion of Purkinje fibers (PFs) to the ventricular myocardium. At this location, on the septal surface of the left ventricle, the insulated left bundle branch split into the uninsulated network of PFs that continued to the free wall anteriorly and posteriorly. The second peak of PF abundance was present in the ventricular apex. Epicardial activation maps correspondingly placed the site of the first activation in the apical region, while some hearts presented more highly located breakthrough sites. Taken together, these results increase our understanding of the physiological pattern of ventricular activation and its morphological underpinning through detailed CCS anatomy and distribution of its gap junctional coupling to the working myocardium.
Keywords: mezibuněčná komunikace; mezerový spoj; Purkyňova vlákna; Connexin 43; konexin 43; Pericardium; Purkinje Fibers; Female; myocardium; optical mapping; zvířata; myši; Cell Communication; Mice; svalové buňky; perikard; ženské pohlaví; Male; Muscle Cells; connexin; Heart Ventricles; immunohistochemistry; Gap Junctions; cardiac conduction system; Animals; mužské pohlaví; srdeční komory